2016
DOI: 10.1155/2016/7896716
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Human Papillomavirus in Colorectal Cancer in Hispanics: A Case-Control Study

Abstract: The role of Human Papillomavirus (HPV) in colorectal carcinogenesis remains elusive. Based on the high incidence of HPV-associated malignancies among Puerto Rican Hispanics, this study aimed to assess the prevalence of HPV infection and viral integration in colorectal tissues in order to evaluate its putative role in colorectal cancer (CRC). In this case-control study, the prevalence of HPV infection in CRC (cases n = 45) and normal colon mucosa from cancer-free subjects (controls n = 36) was assessed by a nes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 52 publications
(69 reference statements)
3
40
0
Order By: Relevance
“…A single case–control study [ 19 ] has been carried out in Puerto Rico so far to relate HPV with CRC. In total, 45 CRC and 36 normal samples were analysed in this study using the PCR technique, and they observed 42% and 2.8% HPV detection positivity ratio in CRC and normal controls, respectively ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…A single case–control study [ 19 ] has been carried out in Puerto Rico so far to relate HPV with CRC. In total, 45 CRC and 36 normal samples were analysed in this study using the PCR technique, and they observed 42% and 2.8% HPV detection positivity ratio in CRC and normal controls, respectively ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer is one of the challenging issues, and its association with HPV infection is under investigation [45] , [46] . In the study by Bernabe-Dones et al [45] of 12 colorectal cancer patients infected with HPV-16 , the E2 gene evaluation for genome status by nested PCR method found that the genome in all the specimens was in an integrated form. They conclude that the integration of HPV-16 genome into the host genome could be a proof of the probable role of HPV in colorectal carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Afterward, to investigate whether E6 oncoprotein could reduce p21 and mdm2 expression through p53 inactivation in p53 wild type tissues, they performed real‐time RT‐PCR analysis; the findings demonstrated that the levels of p21 and Mdm2 mRNA expression in E6 positive/p53‐wild type samples were significantly lower than in their surrounding normal mucosae. Their results proposed a possible role for HPV‐16 in “a subset of colorectal cancer.” Bernabe‐Dones and coworkers in a case‐control study reported a high prevalence of HPV‐16 and genome integration in CRC tissues (Bernabe‐Dones et al, ). In that study, HPV was found in 19 of 45 (42.2%) CRC samples, by nested‐PCR.…”
Section: Colorectal Cancermentioning
confidence: 99%